2018
DOI: 10.1186/s13023-018-0880-9
|View full text |Cite
|
Sign up to set email alerts
|

Annual severity increment score as a tool for stratifying patients with Niemann-Pick disease type C and for recruitment to clinical trials

Abstract: BackgroundNiemann-Pick disease type C (NPC) is a lysosomal storage disease with a heterogeneous neurodegenerative clinical course. Multiple therapies are in clinical trials and inclusion criteria are currently mainly based on age and neurological signs, not taking into consideration differential individual rates of disease progression.ResultsIn this study, we have evaluated a simple metric, denoted annual severity increment score (ASIS), that measures rate of disease progression and could easily be used in cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
59
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 17 publications
7
59
0
Order By: Relevance
“…Electrophysiological studies on vestibular-related networks in a guinea pig model of vertigo suggested ADLL's anti-vertigo effect might be due to its normalisation of abnormal neuronal membrane potentials [12]. ADLL has also been trialled in observational studies via oral administration in monogenic cerebellar ataxia patients, producing significant improvement in gait and other symptoms [13,14]. Another case study that adopted an injectable administration of ADLL for cerebellar ataxia did not find benefit [15], implying that pharmacokinetic parameters are important for its efficacy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrophysiological studies on vestibular-related networks in a guinea pig model of vertigo suggested ADLL's anti-vertigo effect might be due to its normalisation of abnormal neuronal membrane potentials [12]. ADLL has also been trialled in observational studies via oral administration in monogenic cerebellar ataxia patients, producing significant improvement in gait and other symptoms [13,14]. Another case study that adopted an injectable administration of ADLL for cerebellar ataxia did not find benefit [15], implying that pharmacokinetic parameters are important for its efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Another case study that adopted an injectable administration of ADLL for cerebellar ataxia did not find benefit [15], implying that pharmacokinetic parameters are important for its efficacy. Later, oral ADLL was trialled in patients with another lysosomal lipid storage disorder, Niemann-Pick Type C1 (NPC1), where ataxia and dysmetria were reported to improve [14,16]. In addition, cognitive improvements were anecdotally reported by parents of some NPC1 patients who received ADLL treatment, suggesting potential functional benefit beyond the cerebellar system [16].…”
Section: Introductionmentioning
confidence: 99%
“…Having observed unanticipated beneficial effects of ALs in Npc1 -/mice we investigated whether neuroprotective effects also occurred in NPC1 patients treated with ADLL enrolled in an observational clinical study (Cortina-Borja et al, 2018). Total clinical severity scores (with higher values equating to increasing levels of disability (Yanjanin et al, 2010)) were plotted prior to initiation of treatment with Tanganil™ (ADLL), incorporating available retrospective data ( Fig.…”
Section: Neuroprotective Effects Of Adll In Individual-cases Of Off-lmentioning
confidence: 99%
“…6a). The data were also computed as Annual Severity Increment Scores (Cortina-Borja et al, 2018) that measures the rate of disease progression. A mean of -9.1% / year (p<0.001) in ASIS scores was observed (Fig.…”
Section: Neuroprotective Effects Of Adll In Individual-cases Of Off-lmentioning
confidence: 99%
“…On the whole, early onset forms of LSDs are more rapidly progressive than attenuated, late onset forms. This can make patient selection for clinical trials difficult and the interpretation of outcome data problematic . In disorders which are relentlessly, but often slowly, progressive, it is easy to demonstrate efficacy if patients get better, but to prove a treatment stabilizes disease or slows progression is much more challenging.…”
Section: Introductionmentioning
confidence: 99%